2018
DOI: 10.1111/all.13596
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath condensate volatilome allows sensitive diagnosis of persistent asthma

Abstract: Analysis of the exhaled breath condensate volatilome allowed the distinction of paediatric individuals with a medical diagnosis of asthma, identifying those in need of corticosteroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
(51 reference statements)
0
23
0
2
Order By: Relevance
“…Rufo et al . developed a hierarchical model through the use of an electronic nose that analyzed exhaled breath condensate VOCs from children, being able to discriminate children with asthma, defined by medical diagnosis, and those with persistent asthma, based on corticosteroid therapy [52]. Another study conducted in children, revealed that 8 volatile organic compounds were increased in EBC of children with asthma [53].…”
Section: Discussionmentioning
confidence: 99%
“…Rufo et al . developed a hierarchical model through the use of an electronic nose that analyzed exhaled breath condensate VOCs from children, being able to discriminate children with asthma, defined by medical diagnosis, and those with persistent asthma, based on corticosteroid therapy [52]. Another study conducted in children, revealed that 8 volatile organic compounds were increased in EBC of children with asthma [53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a combination of multiple biomarkers may be useful to identify comprehensive individual signatures in ILD patients, which leads to a more personalized medicine [11]. Moreover, exhaled breath-based methods have been studied in the past decades for their applicability in the assessment of airway inflammation and as possible diagnostic tools in several inflammatory lung diseases, e.g., asthma or COPD [26,27]. In this case, a large number of biomarkers in breath have been examined as possible indicators of inflammation, to diagnose and monitor the diseases as well as to evaluate the response to treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…This tool has the potential to assess asthma control and tailoring asthma treatment 147,148 . In a study including participants between 6 and 18 years of age, Cavaleiro Rufo et al showed that the exhaled breath condensate volatilome analysis by an eNose has good accuracy for asthma identification being able to distinguish individuals with diagnosed pediatric asthma from those without the disease 149 . Farraia et al demonstrated that the analysis of the exhaled volatile organic compounds profiles using an eNose could be used as a fast and noninvasive complementary assessment tool for the detection of uncontrolled asthma 147 .…”
Section: Asthma Diagnosis Precision Medicine and Biomarkersmentioning
confidence: 99%